FRI0351 Modulation of the innate humoral immunity in patients with refractory takayasu arteritis treated with biologic agents. (23rd January 2014) - Tombetti, E.; Baldissera, E.; Sabbadini, M. G.; Manfredi, A.
Abstract : Background: Takayasu arteritis (TA) is a relapsing inflammatory large-vessel panarteritis resulting in vessel stenosis, occlusion or aneurysm formation 1, 2 . Medical therapy with steroids and immunosuppressive agents is the cornerstone of TA treatment although a significant proportion of patients are refractory to these regimes 1 . The actual hierarchy among inflammatory signals associated with vascular involvement is so far poorly understood. Anti-TNF and anti-IL-6 receptor agents have been successfully in some TA patients refractory to steroids and conventional immunosuppressive treatments. Objectives: To evaluate whether modulation of the innate humoral immune response occurs differently in TA patients responding or not to anti-TNF agents and tocilizumab (TCZ) and whether this information might be used to predict the response to each treatment. Methods: We have prospectively studied 30 TA patients, 11 treated with steroid and immunosuppressive agents, 14 with TNF-inhibitors and 5 with with TCZ at a single academic Italian center. All patients satisfied ACR criteria for TA classification. Patients stratification was based on: 1) MRI and ultrasonography evidence of vascular progression, 2) clinical response, defined as complete response (CR: absence of imaging progression and of features of active disease while on PD daily dose ≤ 7.5 mg for at least 6 months), partial response (PR: clinical improvement allowing PD reduction >50%) or relapse (loss of CR as above defined). Concentrations of CRP, pentraxin-3 (PTX3), TNF-stimulated gene-6 (TSG-6), procalcitonin and fibrinogen was assessed in parallel by immunochemical assays and compared between respnders and non-responders to biologic agents and with those obtained in non-refractory TA patients and healthy controls. Results: Patients clinical and radiological outcomes were heterogeneous; among refractory TA patients 10 underwent vascular progression after a mean follw up of 46 months; 14 patients achieved CR (9 of whose with subsequent relapse) and two PR. A subgroup of patients on either TNF-inhibitors and TCZ maintained long-lasting CR. CRP variations did not reflect vascular or clinical response in TCZ-treated patients, while it is more informative in patients on TNF-inhibitors. PTX3 levels and CRP patients did not correlate, as well as those of TSG-6. Analysis of the possible predictive role of these parameters is ongoing. Conclusions: In the group of refractory TA, a substantially heterogeneous response to anti-TNF agents or TCZ is evident. A fine characterization of the modulation of signals predominantly generated within inflamed vessels, such as the prototypic long pentraxin PTX3, when correlated with other interacting inflammatory molecules, might provide clues on the relevant pathogenetic events underlying responsive or resistant vascular inflammation in TA. References: Mason JC. Takayasu arteritis--advances in diagnosis and management. Nat Rev Rheumatol 2010;6 (7):406-15. Maksimowicz-McKinnon K, Hoffman GS. Takayasu arteritis: what is the long-term prognosis? Rheum Dis Clin North Am 2007;33 (4):777-86. Disclosure of Interest : None Declared